A Review of the Proboscis Monkey (Nasalis larvatus) in Borneo, with Reference to the Population in Bako National Park, Sarawak, Malaysian Borneo - Mohamad, Bin Kombi; Abdullah, M.T (Chulalongkorn University, 2016)
The Proboscis Monkey (Nasalis larvatus) is endemic to the Island of Borneo. It dominates from the coastal areas to the headwaters of some major rivers. In Sarawak, its distribution occurred in coastal and swamp areas based on previous studies. The population in the Bako National Park, Sarawak is fluctuating when compared to previous studies. The total population of the proboscis monkeys is estimated about 306 individuals compared to the lowest of 111 individuals in 2005. The fluctuating numbers of N. larvatus population is assumed to be at the optimum carrying capacity Bako National Park. There are still large areas of habitat outside the Bako National Park that can support the increasing population size that must be secured to protect a viable population in the long term.